PENGARUH PARTISIPASI ANGGARAN, DESENTRALISASI DAN PROFESIONALISME APARATUR TERHADAP KINERJA APARATUR (PADA SKPD PEMERINTAH KOTA SURABAYA) - CHANDRA SHINTYA, FERIN; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
This research aims to examine the effect of budgetary participation, decentralization and professionalism of apparatus performance. The object of this research is Surabaya Government SKPD as the instituion and the subject is the apparatus of the institution. This research is conducted with quantitative method using questionnaire for the data collection. Twenty six samples had been taken from Surabaya Government SKPD. The independent variable this research are budgetary participation, decentralization and professionalism of apparatus. While the performance of the apparatus is the dependent variable. Based on examination which was conducted using SMARTPLS3, budgetary participation, decentralization and professionalism of apparatus shows positive effect toward work performance of the apaparatus in this research.Keywords : apparatus performance, budgetary participation, decentralization, professionalism of apparatus.